2022
DOI: 10.1155/2022/4071472
|View full text |Cite
|
Sign up to set email alerts
|

Causal Biological Network Model for Inflammasome Signaling Applied for Interpreting Transcriptomic Changes in Various Inflammatory States

Abstract: Virtually any stressor that alters the cellular homeostatic state may result in an inflammatory response. As a critical component of innate immunity, inflammasomes play a prominent role in the inflammatory response. The information on inflammasome biology is rapidly growing, thus creating the need for structuring it into a model that can help visualize and enhance the understanding of underlying biological processes. Causal biological network (CBN) models provide predictive power for novel disease mechanisms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…To obtain mechanistic insight into nicotine’s effects on DSS-induced colitis, we used an enrichment approach that relies on a database of over 800 molecular entities or nodes (e.g., protein activities, complexes, chemicals) with mRNAs known to be regulated by the nodes. The activity of these nodes can be inferred by comparing differential mRNA regulation in experimental data to the mRNAs assigned under each node, taking into consideration the expected directionality of the regulation [ 34 , 35 , 36 ]. Hence, the nodes represent inferred changes in protein activity rather than at the mRNA level.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain mechanistic insight into nicotine’s effects on DSS-induced colitis, we used an enrichment approach that relies on a database of over 800 molecular entities or nodes (e.g., protein activities, complexes, chemicals) with mRNAs known to be regulated by the nodes. The activity of these nodes can be inferred by comparing differential mRNA regulation in experimental data to the mRNAs assigned under each node, taking into consideration the expected directionality of the regulation [ 34 , 35 , 36 ]. Hence, the nodes represent inferred changes in protein activity rather than at the mRNA level.…”
Section: Resultsmentioning
confidence: 99%
“…These enzymes further degrade type II collagen and proteoglycans, which are important components of cartilage. Examples of these enzymes are matrix metalloproteinases and thrombospondin motif metalloproteinases [86,108]. The process causes collagen and proteoglycan particles to be released into the joint space, which in turn promotes the production of additional pro-inflammatory cytokines, such IL-18, which promote inflammation and stimulate the joint.…”
Section: Activation In Inflammatory Diseasesmentioning
confidence: 99%
“…Furthermore, the skin of mice with induced psoriasis, using imiquimod (IMQ), has also exhibited elevated levels of NLRP3 expression, along with increased levels of IL-1b and IL-18. 25 Unbiased sequencing and grid model scoring have revealed that inflammasome activation is the most pronounced in patients with psoriasis, 26,27 and levels of IL-1b and IL-18 are positively correlated with disease severity. 28 These findings suggest that the activation of the NLRP3 inflammasome is present in both patients and IMQ-induced mouse psoriasis models.…”
Section: Psoriasismentioning
confidence: 99%